Knowledge Enhancement about Preventive Orthodontic Treatment for Malocclusion and Stunting in Elementary School Children after Community Empowerment - Nugraha, Alexander Patera; Narmada, Ida Bagus; Noor, Tengku Natasha Eleena binti Tengku Ahmad (Indonesian Journal of Dental Medicine, 2023)
Background:  Nutritional insufficiency and stunting during infant growth and development also causes a delay in the ossification centers and may lead to poor skeletal and dental forms resulted in malocclusion. Early interceptive orthodontics can eliminate or reduce the severity of a developing malocclusion, the complexity of orthodontic treatment, the overall treatment time, and the cost. Proper oral and dental health knowledge and a favorable attitude toward oral and dental health are critical in preventing numerous dental issues such as malocclusion. Purpose: the aim of this community empowerment is to enhance the knowledge of preventive orthodontic treatment for malocclusion and stunting in elementary school children. Methods:  The data was collected at Miftahul Ulum Melirang's Madrasah Ibtidaiyah, or elementary school, in Melirang Village, Bungah District, Gresik, East Java. For the community empowerment program assessment, participants were requested to fill out a Google form for the pre- and post-test to identify the enhancement of knowledge about or preventative orthodontic treatment for malocclusion and stunting in primary school children. Results: The majority of the community empowerment participants understood the presentation on oral and dental health empowerment. The post-test percentage was greater (91.5%) than the pre-test rate (53.75%). Conclusion:  The dental and oral health empowerment program about preventive orthodontics, malocclusion, and stunting was effectively completed, enhancing the knowledge level of elementary school children.